One-step synthesis of Ni/yttrium-doped barium zirconates catalyst for on-site hydrogen production from NH3 decomposition. (12th January 2022) - Wang, Yuanhui; Mao, Xingtong; Yang, Jun; Wang, Jianxin; Guan, Wanbing; Chen, Jieyu; Han, Beibei; Tian, Ziqi
Abstract: On-site produced hydrogen from ammonia decomposition can directly fuel solid oxide fuel cells (SOFCs) for power generation. The key issue in ammonia decomposition is to improve the activity and stability of the reaction at low temperatures. In this study, proton-conducting oxides, Ba(Zr, Y) O3-δ (BZY), were investigated as potential support materials to load Ni metal by a one-step impregnation method. The influence of Ni loading, Ba loading, and synthesis temperature, of Ni/BZY catalysts on the catalytic activity for ammonia decomposition were investigated. The Ni/BZY catalyst with Ba loading of 20 wt%, Ni loading of 30 wt%, and synthesized at 900 °C attained the highest ammonia conversion of 100% at 600 °C. The kinetics analysis revealed that for Ni/BZY catalyst, the hydrogen poisoning effect for ammonia decomposition was significantly suppressed. The reaction order of hydrogen for the optimized Ni/BZY catalyst was estimated as low as −0.07, which is the lowest to the best of our knowledge, resulting in the improvement in the activity. H2 temperature programmed reduction and desorption analysis results suggested that a strong interaction between Ni and BZY support as well as the hydrogen storage capability of the proton-conducting support might be responsible for the promotion of ammonia decomposition on Ni/BZY. Based on the experimental data, a mechanism of hydrogen spillover from Ni to BZY support is proposed. Graphical abstract: Image 1 Highlights: Ni/yttrium-doped barium zirconate (Ni/BZY) was synthesized by single-step synthesis method. Catalyst with pure Ni and BZY phases shows the highest NH3 conversion. The hydrogen-conducting BZY significantly suppresses hydrogen poisoning effect. Hydrogen spillover from Ni to BZY might promote NH3 decomposition significantly.